Kobiety pilnie poszukiwane – system kwotowy w praktyce na przykładzie wyborów samorządowych w Częstochowie - Posyłek, Małgorzata (Polityka i Społeczeństwo, 2021)
The introduction of the quota system, which guarantees men and women with at least 35 percent of places on the electoral rolls, posed a serious challenge for numerous election committees. It forced them to seek out competent women who would like to become involved in politics. It was not an easy task, because the majority of committees placed the women in positions close to the bottom of the lists, which ensured that election success was rather unachievable. This situation caused some women to resign from running for election to the local-government, therefore forcing the election committees to replace them, at a push, with other women, despite a number of male candidates applying to take their place. When it comes to elections results, they proved that the quota system is ineffective, because it favours men, who obtained the highest places on the rolls, and without the implementation of zipping, the number of women in politics will not be increased. This paper aims at presenting the practical aspect of applying the quota system in local elections in Częstochowa.